PERAN PEMERINTAH DALAM MENGIDENTIFIKASI KOMUDITAS USAHA KECIL YANG POTENSIAL SEBAGAI PENYANGGA TAMAN NASIONAL WIASATA TANJUNG PUTING DI DESA SUNGAI SEKOYER, KECAMATAN KUMAI, KABUPATEN KOTAWARINGIN BARAT, PROVINSI KALIMANTAN TENGAH - Hasaruddin Hasaruddin; Rohmelawati Rohmelawati (RELASI : JURNAL EKONOMI, 2022)
Sekonyer Village is the closest to the Tanjung Puting tourist destination. Tens of thousands of foreign tourists visit Camp Leakey, where people from around the world see orangutans. Second, the village of Sungai Sekonyer has been in ruins for the past ten years. Destroyed because it is no longer a comfortable and safe habitat for all kinds of fish. Third, Sekonyer Village is surrounded by several large oil palm plantation companies. an important policy. to encourage the growth of regional economic activities, especially Tanjung Sekonyer Village. need to identify opportunities more efficiently. The results of the study show that the Financial Management Function does not understand well the problems of capital management, implementation in the production function and the procurement function. This is necessary especially to ensure the availability of raw materials so that the production process remains sustainable. The implementation of procurement is still low between 30.7% with an average of 36.1% for all small entrepreneurs. the small business personnel function in the financial/capital management function ranged from 34.4% to trading with an average of 58.7% for all small entrepreneurs. This fairly large number shows that the implementation of the personnel function is quite good, but its implementation is still low. Implementation of administrative functions, ranging from 16.9% to 58% This number is quite large, especially for trading entrepreneurs who have implemented more than 50% of the business development functions of more than 50% of existing small entrepreneurs. the results of tabulation of managerial identification data per economic sector show that the percentage of managerial application is very diverse. The various percentages of implementing managerial aspects show that there are differences in managerial abilities that vary greatly between small entrepreneurs, it can be seen that on average they have the highest percentage (47.0%) in implementing all managerial aspects, and the lowest is (33.0). %). Keywords: sekonyer. Potential small business